Changes in waterbird occurrence and abundance at their northern range boundaries in response to climate warming : importance of site area and protection status - Gaget, E.; Ovaskainen, O.; Bradter, U.; Haas, F. ; 0000-0001-9274-7280; Jonas, L.; Johnston, A.; Langendoen, T.; Lehikoinen, A. S.; Pärt, T.; Pavón-Jordán, D.; Sandercock, B. K.; Soultan, A.; et al. (Animal Conservation, 2024)
Climate warming is driving changes in species distribution, but habitat characteristics can interact with warming temperatures to affect populations in unexpected ways. We investigated wintering waterbird responses to climate warming depending on habitat characteristics, with a focus on the northern boundary of their non-breeding distributions where winter climatic conditions are more extreme. At these Nordic latitudes, climate warming is expected to drive positive changes in species occurrence and abundance, with likely differences in species-specific responses. We analyzed the occurrence and abundance of 18 species of waterbirds monitored over 2,982 surveys at 245 inland wetlands over a 25-year period in Sweden. We used hierarchical modeling of species communities (HMSC) which enabled us to relate species-specific changes to both functional traits and phylogenetic relatedness. We investigated occurrence and abundance changes in response to average temperature, temperature anomalies, site area, site protection status (Natura 2000), and land use in agricultural and urban surfaces. Unsurprisingly, both average temperatures and temperature anomalies were the most important variables influencing positively waterbird occurrence and abundance. For 60% of the species, the effect of temperature anomalies was even stronger in large or protected wetlands. Geese and mallard occurred more often at sites surrounded by agricultural and urban surfaces, respectively, but their occurrence in these habitats was not affected by interactive effects with climate warming. Species abundance was greater inside protected areas only for 11% of the species, but occurrence probability was higher inside protected areas for 44% of the species. Overall, we observed that species thermal affinity was a strong predictor for positive species response to temperature anomalies, and that species sharing similar phylogenetic history had similar relationships with environmental variables. Protection of large wetlands and restoration of the surrounding habitats are two targets for climate change adaptation strategies to facilitate future responses of waterbirds to climate warming.
Keywords: climate change; functional traits; HMSC; phylogeny; protected area; Sweden; waterbirds; wetlands